What We Hold in Trust : Rediscovering the Purpose of Catholic Higher Education - Briel, Don; Naughton, Michael, 1960-; Goodpaster, Kenneth E., 1944- (Book collections on Project MUSE., 2021)
"What We Hold in Trust unfolds in four chapters that will demonstrate how essential it is for the faculty, administrators, and trustees of Catholic universities to think philosophically and theologically (Chapter One), historically (Chapter Two) and institutionally (Chapters Three and Four). It concludes with an examination of conscience for university leaders and recommended reading. It calls for leaders in Catholic universities who understand the roots of the institutions they serve, who can wisely order the goods of the university, who know what is primary and what is secondary, and who can distinguish fads and slogans from authentic reform. These leaders will be in touch with their history and have a love for tradition, and in particular for the Catholic tradition. Without this vision, our universities may grow in size, but shrink in purpose"--